Environmental and genetic effects on body weight in Surti buffalo calves - SORATHIYA, L M; FULSOUNDAR, A B (The Indian Journal of Animal Sciences, 2011)
The data pertaining to birth dates, birth weights and weights at 3, 6 and 12 months age of 317 buffalo calves were collected from records of Livestock Research Station, Navsari from year 2003–2007. Effects of season of calving were found significant on birth weight, BW3 and BW12. The male calves showed higher weight at all age groups but statistically the effect of sex of calves was only found significant at BW3. Effects of sire were significant for BW6 and BW12. Effects of parity were nonsignificant for birth weight but found significant for BW6. The AFC was significantly and negatively correlated with body weights at 3 months but it was nonsignificant with either birth weights or weights at 6 or 12 months. The birth weight were significantly and positively correlated with BW3, BW6 and BW12 suggesting that body weights at early age can be a fairly good indicator of body weight in subsequent period. The sex ratio (male:female calves) during the period of study was 1.22:1. The frequency distribution of calving was maximum during the S3–rainy season (53.94%) and minimum during S2– summer (17.35%).